2015
DOI: 10.1134/s1063778815020209
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the processes e + e − → 2 (π+π−π0) and e + e − → 3 (π+π−) with the aid of the CMD-3 detector

Abstract: Investigation of the Processes e e e + e e e -→ 2 → 2 → 2 (π + ππ 0 ) and e e e + e e e -→ 3 → 3 → 3 (π + π -) with the Aid of the CMD-3 Detector Abstract-The cross sections for the processes e + e − → 2(π + π − π 0 ) and e + e − → 3(π + π − ) at c.m. energies in the range of 1.5-2 GeV were measured with the aid of the CMD-3 detector at the VEPP-2000 collider of the Budker Institute of Nuclear Physics (Novosibirsk, Siberian Branch, Russian Academy of Sciences). The integrated luminosity in the respective exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The enhancement near the pp threshold is also observed in the decays J/ψ(ψ ) → ppπ 0 (η) [5][6][7], J/ψ(ψ ) → ppω(γ) [5,[8][9][10][11]. The sharp peak in the vicinity of N N threshold has been observed in the cross sections of several processes, i.e., e + e − → 6π [12][13][14][15][16] and J/ψ → γη π + π − [17]. These observations led to numerous speculations about a new resonance [5], pp bound state [18][19][20], or even a glueball state [21][22][23] with the mass about double proton mass.…”
Section: Introductionmentioning
confidence: 74%
“…The enhancement near the pp threshold is also observed in the decays J/ψ(ψ ) → ppπ 0 (η) [5][6][7], J/ψ(ψ ) → ppω(γ) [5,[8][9][10][11]. The sharp peak in the vicinity of N N threshold has been observed in the cross sections of several processes, i.e., e + e − → 6π [12][13][14][15][16] and J/ψ → γη π + π − [17]. These observations led to numerous speculations about a new resonance [5], pp bound state [18][19][20], or even a glueball state [21][22][23] with the mass about double proton mass.…”
Section: Introductionmentioning
confidence: 74%
“…This distribution was analyzed for shows the contribution of non-NN channels. The data for total 6π production are calculated from BABAR [14] and CMD-3 [15,16] data. 3 (π + π − ) and 2 π + π − π 0 channels are taken into account,…”
Section: Results Of the Calculationsmentioning
confidence: 99%
“…The inelastic cross section can be expressed in terms of the Green's function of the Schrï¿oedinger equation in the presence of an optical potential. First of all, we are interested in the processes e + e − → 3 (π + π − ) and e + e − → 2 (π + π − π 0 ) because the cross sections of 6π production have a sharp dip near the pp threshold [14][15][16], and this phenomenon is not well understood yet. This feature is expected to be a consequence of the interaction of virtual nucleons, because other contributions should be smooth functions in the energy region under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In a set of experiments it has been shown that the cross sections of e + e − annihilation into pp [1][2][3][4], nn [5] and mesons [6][7][8][9] near the thresholds of N N production reveal the unusual behavior. Namely, in this region the cross sections strongly depend on the energy.…”
Section: Introductionmentioning
confidence: 99%